The Accuracy of Common Hand Injections With and Without Ultrasound: An Anatomical Study. (November 2017) - To, Philip; McClary, Kaylan N.; Sinclair, Micah K.; Stout, Brittany A.; Foad, Mohab; Hiratzka, Shannon; Stern, Peter J.
Background: The aim of the study is to determine the accuracy of hand injections with and without the aid of ultrasound (U/S) into the carpal tunnel, thumb carpometacarpal (CMC) joint, first dorsal compartment (DC) and the radiocarpal (RC) joint.Methods: Four participants of various level of experience injected the carpal tunnel, thumb CMC, first DC, and RC joint into 40 fresh frozen cadaver specimens with blue dye and radiographic contrast. Participants 1 and 2 were injected without U/S guidance, and participants 3 and 4 were injected with U/S guidance. A successful injection was determined by both fluoroscopy and dissection/direct observation. Additional information was recorded for each injection such as median nerve infiltration and evidence of thumb CMC arthrosis.Results: The overall accuracy for carpal tunnel, thumb CMC, first DC, and RC injections were 95%, 63%, 90%, and 90%, respectively. Success was compared with and without U/S guidance. Success rates were similar for each injection site, except the thumb CMC joint, where U/S participants had 25% higher accuracy. In the setting of thumb CMC arthrosis, the incidence of success was 38% for participants with no U/S aid and 72% for participants with U/S aid. There was a significant difference between participants who used U/S with the participant with more U/S experience being more successful.Conclusion: Carpal tunnel, first DC, and RC injections had an accuracy of greater than 90%. Thumb CMC injections have a lower accuracy (63%) and one can improve accuracy with U/S. The accuracy of U/S-guided injections is dependent on the user and their experience.